STRATEGI PENGEMBANGAN TEKNIK PEMBUATAN PRODUKPRODUK KULIT UNTUK MENINGKATKAN KEMAMPUAN KREATIF DI INDUSTRI KECIL/MENENGAH ALAS KAKI CIBADUYUT - Mohamad Arif Waskito (Universitas Trisakti, 2014)
The creative process in industrial product development in small / medium often don't have opportunity to explore the design, especially in industries which only prioritize production activities only. Their activities will be dominated by the action that refers to the effectiveness and efficiency of production. The production process will be determined based on the speed and reduced their production cost. As happens in many footwear industry in Cibaduyut, generally they will act as the industry